Haricot bean agroecology in Ethiopia: Definition using agroclimatic and crop growth simulation models - Simane, B; Wortmann, Charles S.; Hoogenboom, Gerrit (1998)
Bean (Phaseolus vulgaris L.) is an important food and cash crop grown in diverse environmental settings in Ethiopia. Its production is very heterogenous in terms of ecology, cropping system and yield. This study analyses the agroclimatic resources of 18 representative bean growing sites in Ethiopia and assesses the potential yield and moisture deficit stress using DRYBEAN (DSSAT V.3) growth model. Annual rainfall of various locations ranged from 580 mm (Mekele) to 1995 mm (Gore). Seasonal rainfall varied from 270 mm (Babile) to 1650 mm (Gore). The length of the growing period is from only 80 days (Mekele) to more than 220 days (Jimma). Among the agroclimatic variables, annual rainfall, seasonal rainfall, length of the growing period and altitude (temperature) are important factors to cluster the bean growing regions into 3 major and 6 minor homogeneous groups in agronomic sense for strategic planning. Simulated yield potential varied from 1.6 t ha^-1 (Jijiga) to 3.3 t ha^-1 (Bako). Planting date has a significant impact on simulated yield in the sub-humid and semi-arid clusters. Yield losses for each day of delayed planting after the effective onset of rainfall reached up to 60 kg ha^-1 day^-1. Moisture deficit stress was found to be an important limiting factor in the semi-arid and moderately limiting in the sub-humid regions. The analysis established that bean improvement work should focus on the development of high-yielding, long-maturing genotypes for multiple cropping systems in the humid regions. In the semi-arid regions emphasis should be on the development of drought tolerant and early maturing cultivars which fit well with efficient soil and water conservation practices.